Impact of drug coated balloon on left anterior descending artery stenosis at proximal to myocardial bridge - Yuqing Jia; Yangfeng Xie; Ying Li; Huaipeng Zhang; Yanfen Li; Weiming Li; Chuang Li; Yixing Yang; Wenhao Jia; Wenbo Han (Frontiers in Cardiovascular Medicine, 2026)
Background Drug-coated balloons (DCB) represent a novel therapeutic approach for treating native coronary artery disease. However, the clinical outcomes of DCB in patients with left anterior descending (LAD) artery stenosis proximal to a myocardial bridge (MB) remain unclear. This study aims to investigate the effects of DCB in patients with LAD artery stenosis proximal to MB. Method This retrospective cohort study included consecutive patients with LAD artery stenosis proximal to MB who underwent DCB or drug-eluting stent (DES) procedures between January 2020 and July 2021. The DCB group comprised 30 patients treated with DCB alone, while the DES group included 105 patients treated with DES alone. Major adverse cardiac events (MACEs) during a median follow-up of 507 days (IQR 391.5–622.0 days) were defined as a composite of unstable angina requiring hospitalization, acute myocardial infarction, cardiac death, and target lesion revascularization (TLR). Results Both groups exhibited generally comparable baseline clinical and lesion characteristics, except for age and MB systolic compression. Over a median follow-up of 507 days (IQR 391.5–622.0 days), Kaplan–Meier survival analysis revealed no statistically significant difference in MACE-free survival rates between the two groups (73.96%, 95% CI 55.8–98.0 vs. 82.49%, 95% CI 73.9–90.8; Log-rank P = 0.678). Cox proportional regression analysis showed no statistically significant difference in MACEs between DCB and DES patients (HR = 1.58, 95% CI = 0.56–4.45, P = 0.383). Conclusion In this exploratory retrospective study, we did not detect a statistically significant advantage of DCB over DES in treating LAD stenosis proximal to MB. Given the limited sample size, these findings should be considered preliminary and do not support DCB as a reasonable alternative to DES. Larger prospective studies are warranted to validate the potential role of DCB in this specific anatomical setting.